Stress and Deformation Analysis of Composite Geomembrane for Seepage Prevention of Reservoir in Karst Area Under the Action of Reservoir Water Level and Groundwater Level - YANG Yang; LIU Hui; LI Yuqiao (Renmin Zhujiang)
The composite geomembrane has some advantages for seepage prevention treatment of reservoirs in karst area,but it may have adverse effect on the geomembrane due to the joint action of reservoir water level and groundwater level during operation period.In view of this,in order to study the suitability of composite geomembrane for seepage prevention of reservoir in karst area,by taking Lijiaping Reservoir in Qianjiang District,Chongqing City as an example,this paper carries out the finite element analysis through the large finite element software MIDAS GTS NX.The results show that:Under the combined action of reservoir water level and groundwater level,the distribution law of settlement deformation and horizontal deformation of reservoir basin does not differ much,but the decrease of groundwater level will lead to the increase of effective stress of overburden foundation,and then the increase of deformation.When the reservoir water level reaches the check water level and the groundwater level drops to the bedrock surface,the settlement of the reservoir basin,the tensile stress and tensile strain of the geomembrane reach the maximum value.Through calculation,the safety factors of tensile stress and tensile strain are both greater than the permissible safety factor 5.0 required by the code,which indicates that the composite geomembrane has a higher safety margin for seepage prevention.